Legal aid provision in the British Overseas Territories and the Commonwealth Caribbean - Epp, John A. (Cayman Islands Law School Grand CaymanVG, 2003)
Describes in detail and analyzes the legal-aid schemes in the British Overseas Territories and the independent jurisdictions of the Commonwealth Caribbean.